Environmental Politics and the Human Being: A New Interdisciplinary Perspective on Motivational Processes and Sustainable Change Behaviour - Bettina Burger-Menzel (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2016)
Never before has the world been globalized to such an extent, which results in a rapid exploitation of global commons and natural resources and has cross-border effects on biological diversity and climate change. As a consequence, there is a new urgency in making global cooperation in environmental politics work. Although there is a broad consensus that systemic change is needed, progress towards the latter—first, through corresponding global agreements and, second, through effective implementation of those policies at home—seems to lag behind expectations. How can these gaps be explained? And how can new scientific insights help to make environmental politics more effective? Notwithstanding the importance of non-behavioural factors as explanations from the 'outside', the author argues that explanations also have to focus on the 'inside', i.e. individual motivation. The key interest is to better understand the motivational process of individuals who are willing to undergo sustainable change behaviour and to conceptualize the results for further research. This turns human behaviour into an important risk factor in global cooperation and cognition into its relevant feature. This work is on conceptualization with a qualitative methodology and is structured as follows: In order to better grasp the meaning of 'poor' systemic change through environmental politics, the introductory part describes global cooperation as a system and identifies three cognitive blindspots, which need further analysis. As a corresponding literature review proves rich in insights but is too implicit for the further analysis, the author provides her own scheme through which the motivational process is sequenced and linked to the system around the individual. This allows new perspectives on how to discuss change behaviour in globally initiated knowledge production, learning and trial and error adaptations. The conclusions consider what the results obtained so far imply for further research on environmental politics.
urn:nbn:de:hbz:464-20160725-081030-8
Keywords: 320; Global environmental politics; human motivation; cognition; sustainability; systemic change